Excavation results (Scottish Historical and Archaeological Internet Reports, 2010)
Six phases of activity were identified. The remains are described by phase as follows: phase 1 - medieval pits and a well; phase 2 - late medieval or early post-medieval midden deposit; phase 3 - early post-medieval quarry pits; phase 4 - skeletal remains and overlying midden layer; phase 5 - Balmerino House construction; phase 6 - demolition and modern levelling. Radiocarbon dates were obtained on two of the skeletons.